AN OVERVIEW OF THE GREEN BUILDING RATING SYSTEMS IN THE MALAYSIAN CONSTRUCTION INDUSTRY - Yaman, Khariyah Mat; Ghadas , Zuhairah Ariff Abd (International Journal of Psychosocial Rehabilitation, 2020)
It is a goal under the Malaysian government Green Technology Master Plan 2017-2030 (the GTMP) that there shall be an increase from 550 total targeted green buildings in 2020 to a total of 1,750 green buildings by 2030 with substantial targeted emission reduction in both government and private buildings. Evaluating sustainability of a project has, thus, become a necessity. In fact, the GTMP aspires to alter the current landscape of voluntary rating system by making it mandatory. The world has seen the proliferation of green building rating systems as a method to measure sustainability in buildings. In Malaysia, there are at least ten green building rating tools that had been introduced for that very purpose. However, there appears to be no consistency in terms of assessment with different rating tools focusing or giving weight on different criteria of sustainability factors or themes. This paper provides an overview of the existing green building rating systems developed in Malaysia and highlights the differences in the nature and assessment criteria, if they are to be adopted. This paper further discusses on the worldwide debate on the best practice in measuring and reporting on sustainability of a project or building and how the transition from voluntary to mandatory rating system as aspired by the GTMP may be the solution to the issue of “greenwashing”.